The pathogenesis of atherosclerosis - Douglas, G; Channon, K (Elsevier, 2014)
Atherosclerosis is a chronic, inflammatory disease of the arterial wall that underlies many of the common causes of cardiovascular morbidity and mortality, including myocardial infarction (MI), and cerebrovascular and peripheral vascular disease. Early pathological descriptions viewed atherosclerosis as an end-stage degenerative process that inevitably resulted in a generalized narrowing of the arterial lumen. However, progress in our understanding of the pathophysiology and the underlying cellular and molecular mechanisms has revealed that atherosclerosis is a dynamic biological process. The identification of key roles for the endothelium, inflammation and vascular smooth muscle cells (VSMC) in plaque biology has indicated that the cellular composition and biology of the plaque are more relevant to disease progression and complications than luminal narrowing alone, which offers new opportunities to modify and treat different aspects of the disease process. © 2014 Published by Elsevier Ltd.